Pengaruh Penggunaan Tepung Buah Sawit dan Feses Walet Terhadap Pertambahan Bobot Badan, Konsumsi Pakan dan Konversi Pakan Ayam Kokok Balenggek - Farisa, Heru; Hendri, John; Akbar, Syahro Ali; Sari, Rica Mega (Jurnal Peternakan Mahaputra, 2023)
This study aims to determine the effect of body weight gain, consumption, and feed conversion of Kokok Balenggek chickens that consume rations using palm fruit flour and swallow feces. This study used a completely randomized design with three (3) treatments and five (5) replications. Treatment A = 16.6% palm fruit + 6.5% swallow feces, B = 18% palm fruit + 7% swallow feces, C = 21% palm fruit + 7% swallow feces. This research was carried out by direct observation and weighing in the experimental cage. The results showed an increase in body weight in the statistical analysis treatment P1 = 36.12; P2= 39.32; P3= 33.23; Ration Consumption P1= 28.81 P2= 28.52; P3= 24.71 and feed conversion P1= 0.80; P2= 0.73; P3= 0.84. From the research results, it can be concluded that the effect of the ration formulation based on palm fruit flour and swiftlet feces showed no significant difference (P> 0.05) in body weight gain, feed consumption, and feed conversion of Kokok Balenggek chickens.